Effects of crop load on distribution and utilization of 13C and 15N and fruit quality for dwarf apple trees. Issue 1 (December 2017) - Ding, Ning; Chen, Qian; Zhu, Zhanling; Peng, Ling; Ge, Shunfeng; Jiang, Yuanmao
Abstract In order to define the effects of fruit crop load on the distribution and utilization of carbon and nitrogen in dwarf apple trees, we conducted three crop load levels (High-crop load, 6 fruits per trunk cross-sectional area (cm2, TCA)), Medium-crop load (4 fruits cm−2 TCA), Low-crop load (2 fruits cm−2 TCA)) in 2014 and 2015. The results indicated that the15 N derived from fertilizer (Ndff) values of fruits decreased with the reduction of crop load, but the Ndff values of annual branches, leaves and roots increased. The plant15 N-urea utilization rates on Medium and Low-crop load were 1.12–1.35 times higher than the High-crop load. With the reduction of crop load, the distribution rate of13 C and15 N in fruits was gradually reduced, but in contrast, the distribution of13 C and15 N gradually increased in annual branches, leaves and roots. Compared with High-crop load, the Medium and Low-crop load significantly improved fruit quality p < 0.05. Hence, controlling fruit load effectively regulated the distribution of carbon and nitrogen in plants, improved the nitrogen utilization rate and fruit quality. The appropriate crop load level for mature M.26 interstocks apple orchards was deemed to be 4.0 fruits cm−2 TCA.